Circulation of Stereotypes, Health Control, and Social Surveillance of Communal Practices (2020-2021): The Case of the Roma Population in Argentina During the COVID-19 Pandemic - Galletti, Patricia (Acciones e Investigaciones Sociales, 2025)
AbstractThis paper aims to analyze the representational discourses surrounding the Roma during the COVID-19 pandemic in Argentina, comparing them with other regional and global cases to gain a broader perspective. The analysis is based on press clippings and ethnographic records collected during the 2020-2021 period. It explores the role of media discourses in reinforcing stereotypes and conducts an axiological analysis of sanitary control and social surveillance discourses, considering Roma cultural practices related to collective life. The analysis focuses on two dimensions: the historically sedimented representational frameworks circulating in media discourses about the Roma, and the tensions between the individualistic management of the disease (self-care, isolation) promoted by the Argentine government and the World Health Organization (WHO), and the collective practices of the Roma. The results reveal increased stigmatization in the media, exacerbated by the absence of a state program promoting non-discrimination and social equity, which hinders the Roma community's access to healthcare and socioeconomic development in Argentina.
Keywords: COVID-19 Pandemic; Argentina; Stereotypes; Health Control; Rroma